Correction: More on mobility and sedentism: Changes in adaptation from Upper Paleolithic to Incipient Jomon, Tanegashima Island, southern Japan. - Kazuki Morisaki; Fumie Iizuka; Masami Izuho; Mark Aldenderfer (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0314311.].